Almost $τ^\starβ(σ_1,σ_2)$-continuity for Multifunctions (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces new classes of continuous multifunctions defined between an ideal topological space and a bitopological space, called upper almost $τ^\starβ(σ_1,σ_2)$-continuous multifunctions and lower almost $τ^\starβ(σ_1,σ_2)$-continuous multifunctions. Moreover, several characterizations and some properties concerning upper almost $τ^\starβ(σ_1,σ_2)$-continuous multifunctions and lower almost $τ^\starβ(σ_1,σ_2)$-continuous multifunctions are established.
Keywords: upper almost $τ^\starβ(σ_1,σ_2)$-continuous multifunction; lower almost $τ^\starβ(σ_1,σ_2)$-continuous multifunction